Eating Behavior of Autistic Children - Handayani, Maulina; Herini, Elisabeth Siti; Takada, Satoshi (Department of Nursing, Faculty of Medicine, Diponegoro University, 2012)
Association between autism and eating problem has been discussed in US and European countries recently, but there are only a few studies about that matter in Asian countries. Objective: This study provides information about eating behavior in autistic children in comparison with Typically Developing (TD) children in two different countries, which are Japan and Indonesia. Method: Participants of this study were 39 Japanese and 13 Indonesian parents with autistic children and 197 Japanese and 144 Indonesian parents of TD. Ages of subjects were between 3 to 6 years old. Eating behavior was evaluated by using Brief Autism Mealtime Inventory (BAMBI) completed by parents. Result showed that commonly children in both countries had eating behavior problems and children with autistic showed more problems than TD children. It is estimated that autistic children have a delay in eating development that may influence their eating behaviors. It is also reported that cultural background can be considered as another influencing factor in the difference of eating behavior in each country. Conclusion: Our study provided information that Autism children have problem in eating behavior. It needs to be noticed continually by clinicians and parents, although problem in eating behavior is not a core feature of autism; it can be an associate feature in autism. Key words: Autism, Eating behavior, Children